PENGEMBANGAN ALAT EVALUASI BENTUK PILIHAN GANDA MENGGUNAKAN APLIKASI QUIZIZZ MATERI CAHAYA DAN ALAT OPTIK KELAS VIII SMP - Inayatul Ainiyah; Lina Arifah Fitriyah; Nur Kuswanti (Discovery, 2022)
Abstract: Evaluation as one of the learning activities to measure students' abilities in the learning process. The implementation of online learning evaluations is an alternative during the COVID-19 pandemic. The purpose of this study was to determine the process of developing a multiple-choice evaluation tool using the quizizz application on light materials and optical instruments for class VIII SMP. Development of evaluation tools using quizizz using ADDIE. The data obtained during the development implementation were in the form of qualitative data obtained from the validator's comments and quantitative data obtained from validation by three validators. The research results from this development are (1) the development of an evaluation tool is carried out based on the ADDIE model. (2) the results of the validation by three validators got an average score of 95% in the very good category. The developed questions can be used with revisions. Keywords​: ​​ Development, Evaluation tool, Quizizz.